1997
DOI: 10.1007/bf02461950
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphological study of homo- and heterotopic neural transplants

Abstract: Neural transplantation provides an approach to problems in the practice of medicine, as well as to basic questions relating to mechanism of histogenetic processes, synaptogenesis, and the pathogenesis of a number of neuropsychic illnesses. An adequate, and in many respects unique, model for studies of the mechanisms of nerve tissue histogenesis is provided by transplantation of embryonic rudiments of the nervous system into ectopic sites in adult animals, which allows studies of the roles of the microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, it should be emphasized that the data indicating that after retraction of all processes, even neurons which have rounded up, i.e., cells which have lost all signs of differentiation, still have the ability to regenerate [4,5]. Most studies on the regeneration of isolated neurons and on their cultivation and transplantation have been carried out using neurons from embryos or neonates [7,16,19,22]. It has been suggested that poorly differentiated neuronal cells have greater regenerative potential than neurons from adults.…”
mentioning
confidence: 98%
“…However, it should be emphasized that the data indicating that after retraction of all processes, even neurons which have rounded up, i.e., cells which have lost all signs of differentiation, still have the ability to regenerate [4,5]. Most studies on the regeneration of isolated neurons and on their cultivation and transplantation have been carried out using neurons from embryos or neonates [7,16,19,22]. It has been suggested that poorly differentiated neuronal cells have greater regenerative potential than neurons from adults.…”
mentioning
confidence: 98%